Antibody Titers against Canine Parvovirus Type 2 in Vaccinated Dogs Attending Veterinary Clinics - Hernández, Raúl; Aguilar, Carlos; Aguirre, Judyana; Salinas, Luis M; Flores, Byron (Journal of applied veterinary sciences, 2025)
Canine parvovirus type 2 (CPV-2) represents one of the main challenges in veterinary clinical practice. Despite the availability of several commercial vaccines, morbidity and mortality continue to affect even vaccinated puppies. The aim of this study was to evaluate antibody titers against CPV-2 in vaccinated dogs attending veterinary clinics in Nicaragua. A total of 27 dogs aged 3 to 10 months were analyzed. Hemagglutination Inhibition (HI) assays were performed to determine antibody titers. Hematological parameters were measured, and vaccination histories were collected. Among the 27 dogs, 4 (14.8%) had antibody titers of 1:16, 6 (22.2%) had titers of 1:2, 3 (11.1%) had titers of 1:4, 7 (25.9%) had titers of 1:8, and 7 (25.9%) were seronegative. A significant difference was observed in mean corpuscular hemoglobin (MCH) (p = 0.043) between dogs with titers of 1:16 and seronegative dogs, with the latter showing higher MCH values compared to the other groups. Vaccine type and number of doses were associated with titer levels, with better responses observed in dogs that completed the full three-dose schedule. Overall, low levels of antibodies against CPV-2 were found in dogs that had received prior vaccination against this pathogen. These findings emphasize how important it is to monitor vaccination protocols in resource-limited regions.